Development of Kansei Engineering-Based Method for Service Improvement in Hotel Operations - Ni Luh Saddhwi Saraswati Adnyani; Rajesri Govindaraju (Jurnal Rekayasa Sistem Industri, 2020)
The purpose of this study is to develop or improve the Kansei engineering-based method for designing service improvement used in previous studies. Kansei engineering can be integrated with other relevant methods or techniques so that a better method can be produced. This study proposes the development of Kansei engineering-based method that is suitable for designing service improvements in hotel operations by integrating Kansei engineering, text mining, service blueprint, SERVQUAL, Kano model, and QFD. Text mining is used to collect Kansei words by utilizing online customer reviews. Service blueprint is used to determine the service attributes, and SERVQUAL to evaluate current service quality. Kano model is used to classify service attributes into Kano categories. QFD is used to determine customer needs and translate these customer needs into technical characteristics and specifications. The method developed in this study was applied in hotel services in Bali. The results of determining service improvement priorities obtained in this study indicate that service improvements should be focused on the hotel technical requirements which consist of hotel cleanliness standards, availability of housekeeping equipment, professional hotel interior and exterior designers, personnel management, general affair management, employee education and training, and customer relationship management. This method has been successfully applied in the hotel sector. In addition to the hotel sector, this method can also be applied in other service sectors.